Performance and emission characteristics of a diesel engine fuelled with waste cooking oil/diesel fuel blends - Md Isa, Ali; Shahrir, Abdullah; Taib Iskandar, Mohamad (Universiti Malaysia Perlis, 2009)
Organized by School of Mechatronic Engineering (UniMAP) & co-organized by The Institution of Engineering Malaysia (IEM), 11th - 13th October 2009 at Batu Feringhi, Penang, Malaysia.